2002
DOI: 10.1097/00126334-200207010-00007
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and Postpartum Zidovudine Adherence Among Pregnant Women with HIV

Abstract: Adherence to HIV treatment regimens during pregnancy may affect efforts to eliminate vertical transmission and influence the emergence of drug-resistant HIV strains that can affect maternal health and the risk of vertically-transmitted resistant strains. Study objectives were to document patterns of adherence to zidovudine (ZDV) during the perinatal period. Pregnant women with HIV who were seen at public clinics, taking ZDV, and willing to use Medication Event Monitoring Systems (MEMS) caps participated in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 9 publications
1
18
0
Order By: Relevance
“…The other 51 studies [2574] involving 20,153 HIV-infected pregnant women were included; 48 studies reporting 71 adherence estimates were included in the meta-analysis. The remaining three studies [56, 64, 75] reported ART adherence as mean or median adherence and could not be included in the meta-analysis. Kappa agreement was 0.96 between JBN and OUA for inclusion of studies in this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The other 51 studies [2574] involving 20,153 HIV-infected pregnant women were included; 48 studies reporting 71 adherence estimates were included in the meta-analysis. The remaining three studies [56, 64, 75] reported ART adherence as mean or median adherence and could not be included in the meta-analysis. Kappa agreement was 0.96 between JBN and OUA for inclusion of studies in this meta-analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies measured adherence using self-reported questionnaires (n=26, 51%), followed by pill counting (n=9, 18%), and pharmacy refills or claims-based (n=5, 10%). Five studies (9%) used blood drug concentrations (cord blood [43, 44, 50, 74] and red blood cells [36]) to measure ART adherence; one study used electronic medication-events-monitoring system (MEMS caps) [64]. Most of the studies reported adherence during antepartum period (n=39, 76%), four (8%) reported adherence during postpartum period, and eight (16%) reported both antepartum and postpartum adherence rates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Perhaps once the risk of HIV-1 transmission to an unborn child has passed, the tolerance for side effects may diminish. In one study using MEMS caps to track adherence, the overall adherence rate in the post partum period was 34% (23). Bardeguez et al found that adherence rates fell by 10% from prepartum to 48 weeks post partum (24).…”
Section: Discussionmentioning
confidence: 99%
“…diabetes) may improve adherence during pregnancy but increase poor health behaviors postpartum (Zorilla et al, 2003). Although improved ART adherence during pregnancy versus postpartum has been shown in several studies, high rates of non-adherence have been shown in both groups (Ickovics et al, 2002;Tedaldi et al, 2002). Changes in healthcare providers following pregnancy and competing demands of childcare, work and other responsibilities may cause women to neglect their own health postpartum .…”
Section: Introductionmentioning
confidence: 99%